Association between vision and hearing impairment and successful aging over five years. (January 2021) - Gopinath, Bamini; Liew, Gerald; Burlutsky, George; McMahon, Catherine M; Mitchell, Paul
Highlights: A single sensory impairment was associated with a lower odds of successful aging. Hearing-related measures had a greater influence on aging status than vision-related measures. Concurrent vision and hearing loss was not associated with aging status. Abstract: Objective: We aimed to prospectively examine the relationship between vision and hearing loss and successful aging in a cohort of older adults. Study design: We analyzed 5-year data (1997-9 to 2002-4) from 1, 085 adults aged 55+ years, who were free of cancer, coronary artery disease and stroke at baseline and who had complete data on sensory loss. Main outcome measures: Visual impairment was defined as visual acuity <20/40 (better eye), and hearing impairment as average pure-tone air conduction threshold >25 dBHL (500-4000 Hz, better ear). Successful aging was defined as the absence of: disability, depressive symptoms, cognitive impairment, respiratory symptoms and chronic diseases (cancer, coronary artery disease and stroke) at 5-year follow-up. Results: At 5-year follow-up, 243 (22.4%) participants had died and 248 (22.9%) had aged successfully. After multivariable adjustment, participants who had either best-corrected visual impairment or bilateral hearing impairment, versus those who did not have sensory impairment at baseline, had 37% reduced odds of successful aging after 5 years: OR 0.63 (95% CI 0.43-0.94). Concurrent vision and hearing loss at baseline was not associated with 5-year aging status. Participants with moderate and severe hearing handicap at baseline had 50% and 61% reduced odds of aging successfully after 5 years, respectively. Conclusion: The presence of a single sensory impairment in older adults was associated with reduced odds of being disease-free and fully functional or having aged successfully, 5 years later. Objectively measured hearing loss and self-perceived hearing handicap, rather than vision loss, was more likely to negatively influence 5-year aging status.